Task persistence as a competency capable of reducing delinquency in early to mid-adolescence - Walters, Glenn D. (Journal of criminology, 2024)
In an effort to understand the segment of the juvenile population that seemingly ceases engaging in delinquency during adolescence, the relationship between a performance competency (task persistence) and offending was explored in 3,928 youth (2,005 boys and 1,923 girls) from the Longitudinal Study of Australian Children. Three waves of data, with adjacent time periods separated by two years, were used to test the hypothesis that a change in task persistence would correlate with a change in future delinquency. Given that the two dependent variables in this study (delinquency at Time 2 and delinquency at Time 3) followed a negative binomial distribution, negative binomial regression and binomial logistic regression analyses were performed. Results from both analyses confirmed the hypothesis that a rise in task persistence from Time 1 to Time 2 would predict a decrease in delinquency from Time 1 to Time 2 to Time 3 and that a static measure of task persistence at Time 1 would predict a change in delinquency from Time 1 to Time 2. These results suggest that task persistence may be a competency capable of suppressing delinquency during a developmental period in which delinquency ordinarily rises.